Assessment of multidecadal precipitation seasonality in the panama canal watershed - István Gábor Hatvani; Nayara Azevedo de Castro Souza; Russell S. Harmon; Jorge A. Espinosa; Zoltán Kern (Journal of Hydrology: Regional Studies)
Study Region: The 3000 km2 of the Panama Canal Watershed. Study Focus: This study provides insight into the spatiotemporal behavior of precipitation across the PCW11 Panama Canal Watershed utilizing 6-day rainfall records from 29 meteorological stations from 1950 to 2019. The focus interval of 2000–2017 offered the most complete spatiotemporal coverage of the long-term seasonal variability explored by hierarchical cluster analysis. Since the ENSO22 El Niño Southern Oscillation is a key driver of hydroclimate variability in central Panama, differences in the rainfall patterns during the six most prominent El Niño and La Niña events, having respective ENSO indices of > 1.80 and < ˗1.63, were compared to quasi-neutral conditions for the assigned hydroclimatological domains. New Hydrological Insights for the Region: Three spatial domains of similar patterns of seasonal and geographical distribution of rainfall were delineated in PCW by clustering the precipitation-seasonality time series. Stations in the northeastern and northwestern domains of the PCW experience higher average daily precipitation, influenced by the interplay of the annual movement of the ITCZ33 Intertropical Convergence Zone across Panama and weather systems over the Caribbean Sea. The southwestern group of stations reflect the drier conditions prevailing along Panama’s Pacific coast. The most significant ENSO effect is observed in the northeastern part of the PCW, which displays distinct rainfall patterns during the early and late stages of the annual wet season. Since an increase in consecutive La Niña events is expected, it may potentially lead to more precipitation, along with prolonged wet and shorter dry seasons.